"All Enemies, Foreign and Domestic": The Presence of Anti-Latinx Political Rhetoric and Latinxs as Third World Threats in Secondary U.S. Citizenship Curriculum. Issue 2 (February 2021) - Busey, Christopher L.; Corral, Álvaro J.; Davis, Erika L.
Background/Context: Anti-Latinx political discourses have long positioned Latin America and, by extension, U.S. Latinxs as economic, sociocultural, and political threats to the general welfare of the United States. In formal school curricula, this threat narrative has become one of the many political curricular discourses for codifying citizenship as White, and noncitizens as Other (read Black, Indigenous, Latinx, Asian American). Purpose/Objective/Research Question/Focus of Study: The purpose of this study was to illustrate how collapsible Latin American tropes and current anti-Latinx sentiments are reproduced in social studies curricula across the United States. Drawing from and expanding upon Leo Chavez's notion of the Latinx Threat Narrative as a framework, we analyzed secondary social studies curricular standards across all 50 states and the District of Columbia to determine how anti-Latinx and anti-Latin American political rhetoric is reified in U.S. civic and citizenship-based curriculum. The following research question guided our study: In what ways do secondary U.S. civic and citizenship education curricular standards situate Latinxs and Latin America within the Latinx Threat Narrative and current anti-Latinx political sentiment? Research Design: To carry out our study, we conducted a critical content analysis of secondary social studies curricular standards with a particular focus on U.S. history, civics, and economics content standards and benchmarks across all 50 states and the District of Columbia. Situating our theoretical framework as an analytic tool, we systematically extracted and analyzed all standards with explicit or implicit references to Latinxs and Latin Americans. Findings/Results: Findings indicate that Latin America and, by extension, Latinxs are regularly situated as social and political dangers to the overall welfare of the United States, suggesting the presence of what we refer to as the Latinx Third World Threat Narrative. We argue that this hemispheric homogenization of Latinx peoples in curricular standards flattens important historical and cultural distinctions, thereby facilitating exchange of anti-Latinx stereotypes present in contemporary political rhetoric. We also show how U.S. Latinx civic agency is encoded as an illicit, corrupt, and destabilizing force. Conclusions/Recommendations: In light of our findings, we suggest that educators pay specific attention to the political amalgamation of Latinx subjectivities. Additionally, policy advocates and educators must move beyond understanding curricular representation as just an impediment to students' heritage knowledge and begin to understand state-backed curricular standards as part of a larger political apparatus.